Challenges in cleaning for frozen food SMEs: current and suggested cleaning program - Khalid, Nurul Izzah; Ab. Aziz, Norashikin (Malaysian Society of Agricultural Engineers, 2019)
Cleaning can be costly and complex especially for SMEs. Food SMEs have a restricted budget and knowledge to implement an effective cleaning program. A study was conducted in a frozen food SME to investigate the current cleaning practice. Physically and microbiologically cleanliness was set as the cleaning target. Results show that the current cleaning program was unable to reach a physically clean condition. A new cleaning program was suggested for this frozen food industry. The new cleaning program was expected to help this factory to reach physically and microbiologically clean conditions. A clean environment can lead to better food product quality and appearances.